Response mechanism of subtropical forest carbon balance to climate change based on InTEC model - Zhang, Yuan; Li, Kai; Zhang, Xiaoling; Huang, Mingliu; Wang, Qingjun; Zhang, Shihong; Zhang, Fan; Li, Hong (Frontiers in Forests and Global Change, 2025)
IntroductionSubtropical forests play an important role in the global carbon cycle, and their carbon balance response mechanism to climate change not only has important theoretical value, but also has practical reference significance for forest management and decision-making in response to climate change in similar ecosystems in the future.MethodsTaking Zhejiang Province, China as an example, a series of relevant data were collected, including forest distribution, meteorological data, soil data, nitrogen deposition data, etc. The optimized InTEC model was used for simulation to predict the net ecosystem productivity of forests in Zhejiang Province under different climate scenarios at a hundred year scale in the future, and the temporal and spatial sequence changes were analyzed. Then, combined with the spatiotemporal variation characteristics of meteorological data, analyze the response mechanism of subtropical forest ecosystem carbon cycle to climate change. The age of the Result forest and climate change factors have a significant impact on the forest’s carbon sequestration capacity. In the past forest age stage, the climate factors that had the greatest impact on the net ecosystem productivity of forests were temperature, precipitation, and solar radiation, with correlation coefficients of 0.56, 0.84, and −0.79, respectively. After the forest matures, the correlation between net ecosystem productivity and temperature is the highest and negatively correlated under different climate scenarios. This indicates that there are significant differences in the response of forests to climate change at different times. The response of Discuss forests to climate change varies significantly at different stages, therefore different management measures should be taken according to forest age, especially in subtropical forests. This discovery is of great significance for understanding the influencing factors and driving mechanisms of forest carbon sink function, and also provides a reference for predicting future forest carbon cycle dynamics.